The Authority Of Military Justice To Try Military Doctors Who Perform Malpractices In Non-Government Hospitals - Tambunan, Johannes; Pramono, Budi (Kertha Patrika; Vol 45 No 3 (2023)DO - 10.24843/KP.2023.v45.i03.p07, 2023)
In every action of a military doctor in a hospital, there are certainly interesting potential problems related to criminal acts in general or the military as well as in the field of health law. The aims of study were to analyze the form of regulations and legal issues for military doctors who practice in non-government hospitals; analyze authorities and justice mechanisms that prosecute malpractice acts of military doctors in non-government hospitals. The type of research was normative juridical. The approach study used a statute approach and conceptual approach. Legal materials obtained from research, literature study, statutory regulations and legal articles. The results of the research explain that a military doctor is a soldier with strata officer status or rank who can practice both in private practice and in non-government hospitals based on regulations, in accordance with the condition that a doctor must have a doctor's registration letters and a practice license. The military judiciary has authority over every T soldier who commits a crime, be it a military crime or a general crime, including military doctors who are definitely officers, if they commit a crime or malpractice at a place of practice in a non-government hospital.